1982
DOI: 10.1073/pnas.79.4.1158
|View full text |Cite
|
Sign up to set email alerts
|

Growth of hybridoma cells in serum-free medium: ethanolamine is an essential component.

Abstract: A serum-free medium supplemented with a few growth factors was devised to grow lymphocyte hybridomas. The medium was developed with the hybridoma line MPCll-BL, a fusion product between a mouse plasmacytoma cell line (MPCllTG70na3) and mouse (BALB/c) spleen cells. In the process of developing the-medium, ethanolamine was found to be an essential growth factor for the hybridoma. Phosphoethanolamine at 10-fold higher concentration could substitute for ethanolamine. Long-term cultivation of the cells was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(93 citation statements)
references
References 15 publications
(18 reference statements)
2
91
0
Order By: Relevance
“…In addition, Hiroki Murakami et al. found that ethanolamine is essential for the serum‐free cultivation of hybridomas and developed the supplement, ITES, which consists of ITS plus ethanolamine 89. Various other supplements were designed for different cell types and cultivation purposes, with the aim of the addition of various trace elements to protein‐free culture media.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…In addition, Hiroki Murakami et al. found that ethanolamine is essential for the serum‐free cultivation of hybridomas and developed the supplement, ITES, which consists of ITS plus ethanolamine 89. Various other supplements were designed for different cell types and cultivation purposes, with the aim of the addition of various trace elements to protein‐free culture media.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…7) HB4C5 cells were cultured in an ERDF medium supplemented with 100 units/mL of penicillin, 10 mg/mL of streptomycin, 10 mg/mL of insulin, 20 mg/mL of transferrin, 20 mM ethanolamine, and 25 nM sodium selenite (ITES-ERDF) at 37 C under 5% CO 2 in humidified air. 8) Human peripheral blood lymphocytes (PBLs) were obtained from peripheral blood of a healthy female donor as described in a previous report. 9) Briefly, human peripheral blood diluted with an equal volume of PBS was centrifuged at 800 Â g for 20 min on a lymphocyte separation medium (Nycomed Pharma, Oslo, Norway).…”
Section: Methodsmentioning
confidence: 99%
“…HB4C5 cells, which produce human lung cancer specific monoclonal IgM, were fusion products of a human lymphocyte and a human fusion partner NAT-30 cells [6]. HB4C5 cells were maintained in ERDF medium (Kyokuto Pharmaceutical, Japan) supplemented with 10/.tg/ml of insulin, 20/lg/ml of transferrin, 20/IM ethanolamine and 25 nM sodium selenite (ITES-ERDF) at 37°C under humidified atmosphere of 5% COJ95% air [7].…”
Section: Cells and Cell Culturementioning
confidence: 99%